"Bringing the State Back In" to the Empire Turn: Piracy and the Layered Sovereignty of the Eighteenth Century Atlantic. Issue 2 (20th August 2016) - Shirk, Mark
Abstract: Through most of the seventeenth century, European states used an "imaginary" boundary in the Atlantic referred to as "the line" to cordon off the affairs of Europe from those in the New World. The line structured colonial rule, captured in the phrase "there is no peace beyond the line." However, by the middle of the eighteenth century, the idea of "the line" no longer held. Common explanations ranging from the rise of capitalism, technology, and interstate competition do not explain this shift. Instead, I argue that the "golden age of piracy" was instrumental. In giving this explanation, I argue that the empire turn in IR has under-theorized the tensions between state and empire in the modern era. I introduce the state–empire hybrid polity as one that is constantly mediating the tensions between the difference characteristic of empire and the integration of the state. "The line" was how European states mediated this tension in the seventeenth century. Pirates took advantage of the open markets and ungoverned spaces inherent in the line, causing a crisis in colonial rule. To defeat piracy and make the world safe for trade, these tensions needed to be remediated and "the line" transformed. As an unintended consequence, this put further strain on England's North American empire.